Colorectal cancer and therapy response: a focus on the main mechanisms involved - Tirendi, Sara; Marengo, Barbara; Domenicotti, Cinzia; Bassi, Anna M.; Almonti, Vanessa; Vernazza, Stefania (Frontiers in Oncology, 2023)
Introduction: The latest GLOBOCAN 2021 reports that colorectal cancer (CRC) is the second leading cause of cancer-related death worldwide. Most CRC cases are sporadic and associated with several risk factors, including lifestyle habits, gut dysbiosis, chronic inflammation, and oxidative stress. Aim: To summarize the biology of CRC and discuss current therapeutic interventions designed to counteract CRC development and to overcome chemoresistance. Methods: Literature searches were conducted using PubMed and focusing the attention on the keywords such as “Current treatment of CRC” or “chemoresistance and CRC” or “oxidative stress and CRC” or “novel drug delivery approaches in cancer” or “immunotherapy in CRC” or “gut microbiota in CRC” or “systematic review and meta-analysis of randomized controlled trials” or “CSCs and CRC”. The citations included in the search ranged from September 1988 to December 2022. An additional search was carried out using the clinical trial database. Results: Rounds of adjuvant therapies, including radiotherapy, chemotherapy, and immunotherapy are commonly planned to reduce cancer recurrence after surgery (stage II and stage III CRC patients) and to improve overall survival (stage IV). 5-fluorouracil-based chemotherapy in combination with other cytotoxic drugs, is the mainstay to treat CRC. However, the onset of the inherent or acquired resistance and the presence of chemoresistant cancer stem cells drastically reduce the efficacy. On the other hand, the genetic-molecular heterogeneity of CRC often precludes also the efficacy of new therapeutic approaches such as immunotherapies. Therefore, the CRC complexity made of natural or acquired multidrug resistance has made it necessary the search for new druggable targets and new delivery systems. Conclusion: Further knowledge of the underlying CRC mechanisms and a comprehensive overview of current therapeutic opportunities can provide the basis for identifying pharmacological and biological barriers that render therapies ineffective and for identifying new potential biomarkers and therapeutic targets for advanced and aggressive CRC.